Burton Egbert Stevenson papers - Stevenson, Burton Egbert, 1872-1962.
Correspondence with poets and other writers, drafts and copies of Stevenson's writings, negotiations with publishers relating to the compilation of Stevenson's anthologies, comments on the origin of quotations, and obscure biographical data on literary figures. Includes requests for reading material from soldiers on the front during World War I as well as correspondence and administrative files from his service as European director of the American Library Association's Library War Service, including material on the American Library in Paris. Individuals discussed in Stevenson's correspondence include writers such as Joaquin Miller, Clement Clarke Moore, and Ella Wheeler Wilcox. Correspondents include Charles Agnew MacLean, Carl Hastings Milam, Herbert Putnam, and M. Llewellyn Raney.
Anthologist, author, and librarian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: MacLean, Charles Agnew, -- 1880-1929 -- Correspondence; Milam, Carl Hastings, -- 1884-1963 -- Correspondence; Miller, Joaquin, -- 1837-1913.; Moore, Clement Clarke, -- 1779-1863.; Putnam, Herbert, -- 1861-1955 -- Correspondence; Raney, M. Llewellyn -- 1877- -- Correspondence; Wilcox, Ella Wheeler, -- 1850-1919.; American Library Association; American Library Association. -- Library War Service; American Library in Paris; Libraries -- France -- Paris; Libraries -- United States; Libraries -- United States -- Societies, etc; World War, 1914-1918 -- Libraries; Anthologists; Authors; Librarians